KAJIAN KOMPREHENSIF PENGGUNAAN DANA KREDIT PADA MITRA BINAAN PROGRAM KEMITRAAN DAN BINA LINGKUNGAN PT. JASA RAHARJA MANADO - Rompas, Vichri V.; Ilat, Ventje; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study aims to examine the use of Credit Funds in Partnership and Community Development Program Partners of PT. Jasaraharja Manado. The research method is qualitative research in which the informants consist of Jasaraharja staff and Foster Partners. From the results of the study shows that the procedures for distribution of programs, partnerships and environmental development of PT. Jasa Raharja branch of Manado is in accordance with the regulation of the Minister of BUMN PER-02 / MBU / 7/2017 article 11.Â  But regarding the fostered partners, there were still Foster partners who used the credit that was not in accordance with the proposal submitted.Â  The results of the research also found problems in the credit administration system and in terms of credit supervision. Efforts to overcome obstacles in the credit administration system are using the Management by Objectives approach. Efforts to overcome constraints in credit supervision include conducting training and supervision for Foster Partners.